Heat-induced aggregation and gelation of proteins from edible honey bee brood (Apis mellifera) as a function of temperature and pH. (June 2019) - Mishyna, Maryia; Martinez, Jean-Jacques Itzhak; Chen, Jianshe; Davidovich-Pinhas, Maya; Benjamin, Ofir
Abstract: Edible insects offer a huge potential as a new source of proteins for food and feed and as a promising functional agent. In this regard, our study aimed to evaluate the effect of pH and temperature on aggregation and gelation of honey bee brood ( Apis mellifera ). Aggregation of soluble proteins was dependent on temperature and pH value and the highest coagulation was reached at 85 °C at pH 5 and 7 (73.7 and 68.4%, respectively). Changes in protein surface hydrophobicity, net charge and amount of available and buried sulfhydryl groups demonstrated the contribution of either covalent or non-covalent intermolecular interactions resulted in aggregation at various pH. The least gelation concentration of raw powder from honey bee brood varied from 5 to 11% on raw powder basis at pH 7 and 3, respectively. Moreover, the effect of pH on rheological and textural properties, as well as gel microstructure from honey bee brood is discussed. Therefore, freeze dried raw powder of honey bee brood has rich nutritional value and demonstrated gelation concentration comparable to conventional protein sources that reveal its potential as an ingredient for insect-based gel product. Graphical abstract: Image 1 Highlights: Coagulation of honey bee brood proteins is a pH and temperature-dependent. Size of coagulated soluble proteins varied as a function of pH and temperature. Heating induced changes in surface hydrophobicity, charge, SH groups of proteins. Least gelation concentration of honey bee brood raw powder – 5% on raw basis at pH 7. Textual properties and gel microstructure were affected by pH alteration.